2016
DOI: 10.1098/rspb.2016.0731
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in different pigmentation genes are associated with parallel melanism in island flycatchers

Abstract: The independent evolution of similar traits across multiple taxa provides some of the most compelling evidence of natural selection. Little is known, however, about the genetic basis of these convergent or parallel traits: are they mediated by identical or different mutations in the same genes, or unique mutations in different genes? Using a combination of candidate gene and reduced representation genomic sequencing approaches, we explore the genetic basis of and the evolutionary processes that mediate similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 53 publications
4
71
0
Order By: Relevance
“…If true, this contrasts with the recessive inheritance pattern of black throat colour in goldenwinged warblers, which was predicted to be a recessive Mendelian trait [56] and recently confirmed with genomic data [18]. Other melanin-based traits in birds with known genetic basis are consistent with dominant [57] or partially dominant inheritance [14].…”
Section: (B) Candidate Genes and Functional Interpretationsmentioning
confidence: 80%
See 3 more Smart Citations
“…If true, this contrasts with the recessive inheritance pattern of black throat colour in goldenwinged warblers, which was predicted to be a recessive Mendelian trait [56] and recently confirmed with genomic data [18]. Other melanin-based traits in birds with known genetic basis are consistent with dominant [57] or partially dominant inheritance [14].…”
Section: (B) Candidate Genes and Functional Interpretationsmentioning
confidence: 80%
“…For instance, several studies have consistently identified coding changes as well as putative regulatory differences in the gene agouti signalling protein (ASIP) between birds with melanic and non-melanic plumage patches [1,14,18,28]. Our assay identified 72 SNPs within 50 kb of the ASIP coding region, but none were highly differentiated between myrtle and Audubon's warblers (average F ST in this region ¼ 0.02, lower than the genome-wide average of 0.045).…”
Section: (B) Candidate Genes and Functional Interpretationsmentioning
confidence: 87%
See 2 more Smart Citations
“…The eumelanistic morphs in different isolated populations of Chestnut-bellied Monarch Monarcha castaneiventris on the Solomon Islands are the result of two different mutations. The eumelanic plumage of birds on the small island of Santa Ana is the result of a variation of the MC1R, while equally black birds on two other small islands, Ugi and Three Sisters, possess a mutation of the agouti gene (Uy et al 2016).…”
Section: Melanism and Mc1rmentioning
confidence: 99%